Beispiel Nr: 04
$ \text{Gegeben:}a \log_b{(cx+d)}+f=0 \\ \\ \text{Gesucht: } \text{Lösung der Gleichung} \\ \\ a \log_b{(cx+d)}+f=0 \\ \textbf{Gegeben:} \\ a=3 \qquad b=4 \qquad c=-2 \qquad d=4 \qquad f=10 \\ \\ \textbf{Rechnung:} \\ 3 \cdot log_{4}{(-2x+4)}+10 =0 \\ 3 \cdot log_{4}{(-2x+4)}+10=0 \qquad /-10 \\ 3 \cdot log_{4}{(-2x+4)}=-10 \qquad /:3 \\ \log_{4}{(-2x+4)}=-3\frac{1}{3} \qquad /4^{..} \\ -2x+4=4^{-3\frac{1}{3}} \qquad / -4 \qquad / :-2 \\ x=\dfrac{4^{-3\frac{1}{3}}-4}{-2} \\ x=2 $